2014
DOI: 10.1007/s00345-014-1388-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of two different incision techniques for surgical treatment of stress urinary incontinence with concomitant anterior vaginal wall prolapse

Abstract: Both incision techniques have satisfactory outcomes in the surgical treatment of SUI with cystocele; nevertheless, the postoperative complications favor the double-incision technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…[24] In our study, all the scores of KHO which is used to assess quality of life, improvement and the overall satisfaction was 88.4%, according to VAS in agreement with others [23,36] in which improvement, …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[24] In our study, all the scores of KHO which is used to assess quality of life, improvement and the overall satisfaction was 88.4%, according to VAS in agreement with others [23,36] in which improvement, …”
Section: Discussionsupporting
confidence: 90%
“…In other studies [13,23] 11 and 6 patients had postoperative urine retention, respectively. Yonguc et al [36] , reported postoperative urinary retention in nine women (11.3%) in Group 1 (repairing cystocele through one incision), which required an indwelling catheterization for 7-14 days. There was no UR in Group 2 (cystocele repaired through two incisions).…”
Section: Discussionmentioning
confidence: 99%
“…Yonguc et al compared a double incision technique and a single incision technique and suggested that both techniques have satisfactory outcomes in a concomitant cystocele operation with TOT. No concomitant hysterectomy was performed in the same session . The operation time was significantly lower in a single incision technique.…”
Section: Discussionmentioning
confidence: 99%
“…Halbuki anterior tek bir insizyon kullanılması işlemi kolaylaştırırken daha iyi anatomik düzeltme sağlamaktadır. Tek insizyon ile mid üretral cerrahisinin başarısının etkilenmediği gösterilmiştir (29,30). Çalışmamıza katılanlar ve sistosel onarımı ile midüretral sling operasyonunu beraber yapanların %31,8'i tek anterior insizyon uyguluyorken, %68,2'si ilk önce üretra altından insizyon ile mid-üretral sling operasyonunu gerçekleştirip altından başka bir insizyon ile anterior vajinal duvar onarımını gerçekleştiriyordu.…”
Section: Bulgularunclassified